Clinician Experiences of Care Provision in the Correctional Setting: A Scoping Review. (October 2020) - Simon, Lisa; Beckmann, David; Stone, Martha; Williams, Rachael; Cohen, Marya; Tobey, Matthew
Little is known about the experiences of correctional health care providers and how their experiences impact the correctional health care system. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols guidelines, multiple databases were searched. Each abstract was read by two reviewers with a third for consensus as needed. Full-text articles were selected through a second round of review. Of 4, 467 citations, 61 were selected for full-text evaluation and 23 were ultimately included. Major themes identified were the distinctive working environment, burnout, and the presence of ethical dilemmas, including the tension between security and clinical considerations. This scoping review identified a limited number of articles centered on the health care provider experience in the correctional setting.